Pengaruh Black Carbon Dan Sulfur Terhadap Koefisien Grip Bahan Ban Luar Dengan Batikan Bulat Di Lintasan Beton Pada Kondisi Kering Dan Basah - Soleh, Ihwan Basirun Nur; , Ir. Pramuko IP., MT (2016)
This study aims to determine the effect of black carbon and sulfur to the grip coefficient of the tire material with cement round groove on the track, as well as studying the grip coefficient comparison of test results between the artificial and the market compound. Tire works by utilizing the friction force has a surface with the road surface, the friction force is referred to as the grip, the grip can be enhanced by improving the coefficient of friction between the tire to the road, because the road surface is the amount of a constant that can not be changed, to fix a friction coefficient by improving quality compound tire. Vulcanised rubber compound in batikan specimen molds shaped like a round later and tested tire grip coefficient. To determine the effect of black carbon and sulfur compound then made three compositions by the number of black carbon and sulfur are different. Compound 1 using 50 phr black carbon and 3 phr sulfur, compound 2 using black carbon 55 phr and sulfur 3.5 phr and compound 3 using black carbon 60 phr and 4 phr sulfur. The compound then vulcanised and test the coefficient of grip. To determine the physical properties of compound hardness testing and tensile testing. The test results showed the addition of the load when testing the coefficient of grip on the tire material round groove can increase the coefficient of grip. Increasing the amount of sulfur and carbon resulted in a decrease in the coefficient of grip on the tire material beyond groove round. The more the amount of sulfur and black carbon are mixed, the higher hardness materials produced tires, but lowers its strength. Materials tires groove round with the highest amount of sulfur and carbon, has the lowest wear.